Meningkatkan Pemikiran Kritis dalam Pendidikan Fisika melalui AI: Tinjauan Literatur Sistematis tentang Tren dan Implikasi Pedagogis - Hendarman Lubis; Vina N. Van Harling; Victor Bintang Panunggul (Universitas Garut, 2025)
This study aims to map research trends and analyze the pedagogical role of Artificial Intelligence (AI) in enhancing students' critical thinking skills in physics education. Employing a Systematic Literature Review (SLR) method guided by PRISMA protocols and enriched with bibliometric analysis, this study reviewed Scopus-indexed articles published between 2015 and 2025. Based on 42 mapped articles and an in-depth analysis of 12 key studies, the results indicate a significant trend shift post-2023 toward the use of Generative AI. Key findings reveal that